The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/d0cc02206c
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(ii)-modified covalent-organic framework film for electrocatalytic oxidation of 5-hydroxymethylfurfural (HMF)

Abstract: Electrochemical oxidation of 5-hydroxymethylfurfural (HMF) is a promising synthetic route for 2,5-furandicarboxylic acid (FDCA) production. Here, we prepared a nickel(II)-modified covalent-organic framework (COF) film TpBpy-Ni@FTO for HMF electrooxidation. With a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…52,53 MOFs and COFs have begun to be used for this reaction but have thus far only been applied in highly alkaline conditions. 37,57 Similarly, high conversion rates and faradaic efficiency values (both above 95%) have been noted for transition metal based catalysts, but only in highly alkaline conditions (0.1 to 1.0 M KOH). [54][55][56][58][59][60][61][62][63][64] As discussed below, we believe that the key to the high performance of this system in weakly basic conditions lies in the unique active site conguration.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…52,53 MOFs and COFs have begun to be used for this reaction but have thus far only been applied in highly alkaline conditions. 37,57 Similarly, high conversion rates and faradaic efficiency values (both above 95%) have been noted for transition metal based catalysts, but only in highly alkaline conditions (0.1 to 1.0 M KOH). [54][55][56][58][59][60][61][62][63][64] As discussed below, we believe that the key to the high performance of this system in weakly basic conditions lies in the unique active site conguration.…”
Section: Resultsmentioning
confidence: 71%
“…35,36 In the last year, transition metal sites in MOFs explored as active sites for HMF oxidation. 37,38 We moved to systematically study the structure and activity of these missing hydroxyl linker defect NiO 4 sites within Ni-MOF-74 with the aim of generating an in depth understanding of how they function in an electrocatalytic context and by doing so, extract out valuable design principles that can be generalized across a wide array of systems.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of electrocatalytic methods, Cai et al. recently reported the preparation and utilization of a Ni‐modified COF film, specifically TpBpy‐Ni@FTO [Ni II acetate into a 2D COF, triformylphloroglucinol (Tp) 5,50‐diamino‐2,20‐bipyridine (Bpy) fluorine‐doped tin oxide (FTO)], for HMF electrooxidation to FDCA [39b] . By applying a constant potential, the researchers achieved a high HMF conversion (96 %) to FFCA (34 % yield) and FDCA (58 % yield) as the products.…”
Section: Electrochemical Oxidation Strategiesmentioning
confidence: 99%
“…In 2020, Cai et al investigated HMF oxidation to FDCA using nickel (II)-modified covalent-organic framework (COF) film TpBpy-Ni@FTO [71]. However, LSV scan with 0.1 M LiClO 4 (pH of 13) and 0.5 M 5-HMF revealed that the potential was about 1.7 V for 0.1 mA/cm 2 .…”
Section: -Hydroxylmethylfurfuralmentioning
confidence: 99%